2018
DOI: 10.1016/j.hpb.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Response and outcome from fluid resuscitation in acute pancreatitis: a prospective cohort study

Abstract: The serum biomarkers did not discriminate between fluid responsive and refractory patients. Refractory patients at 6-8 h had more severe disease on admission, did not benefit from additional fluids and had a worse outcome. New approaches to guide fluid resuscitation in patients with AP are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…3). The finding is consistent with studies which showed that rapid and high volume fluid therapy increases the risk of pulmonary edema and exacerbates respiratory failure in AP [13,24]. Our study has several limitations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3). The finding is consistent with studies which showed that rapid and high volume fluid therapy increases the risk of pulmonary edema and exacerbates respiratory failure in AP [13,24]. Our study has several limitations.…”
Section: Discussionsupporting
confidence: 91%
“…The primary clinical outcome measure was the rate of NPPV. We have selected NPPV as the primary endpoint because respiratory dysfunction/failure is the most common organ system affected, and because we have demonstrated that the most frequently noted consequence of ERFT is respiratory dysfunction [24]. In our setting, NPPV is the most commonly used means of organ support and it is frequently used in the general ward setting, and has been shown to reduce the need for ICU admission and invasive ventilation [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We maintain that shortening the duration of all organ failure is an important treatment target and should be routinely reported. This is illustrated by recent findings that early initiation of aggressive fluid therapy may be helpful, but if delayed 6–8 hours after admission the risk of POF and mortality may be increased 9. The frequent early onset of POF and impact of its duration underline the importance of door-to-needle time10 and the duration of POF as an outcome in clinical trials of new treatments for AP.…”
mentioning
confidence: 99%
“…Klinische Auswertungen zu Patienten auf Überwachungsstationen belegen, dass Informationen über Oligurie, Anurie bzw. eingeschränkte Diuresemengen als unabhängige, hochsensitive und frühzeitige Marker für die Diagnose eines AKI verwendet werden können[88][89][90]. Limitierend ist, dass eine genaue Bilanzierung und Bestimmung der stündlichen Diuresemenge nur mittels Blasenkatheters und bei entsprechendem Personalschlüssel gewähr-Biomarker zur Diagnostik des AP-AKI.…”
unclassified